GESTION DES DECHETS BIOMEDICAUX A BRAZZAVILLE CAPITALE DU CONGO - Mouankié Jean Bertin; Abéna Ange Antoine; Okémy Andissa Nadège; Diakouka Diambalou Rancia C (European Scientific Journal, ESJ, 2015)
The biomedical garbage (DBM) represents a major risk for the human health and constitutes a public power preoccupation. The present survey has for objective to contribute to the improvement of the management of the biomedical garbage in Congo. It is a prospective survey led in four sanitary structures of Brazzaville. It is about the hospitals of basis of Talangaï and Makélékélé, of the National Center of Blood Transfusion and the National Laboratory of Public Health. The Protocol consisted in an observation, a cross-examination through a questionnaire under - tense by a card of investigation to value the following variables: typology of the garbage, fashion of elimination of the garbage, incidents or accidents of manipulation, formation of the staff. The results are constituted of 36% of positive answer on the production of the syringes for the cutting and pungent garbage, and of 19, 61% of blood for the infectious garbage. 30, 48% of positive answers have been expressed concerning the use of the incinerator for the elimination of the garbage. 71, 13% of positive answers have been expressed concerning the existence of accidents of manipulation of the biomedical garbage. On the other hand 44, 29% of positive answers signaled the existence of the vicinal cover and that 54, 29% of the agents had received a formation on the biomedical garbage management. The biomedical garbage treatment in the studied public sanitary structures is even rudimentary and requires the setting up of a real national plan of biomedical garbage management.